2015
DOI: 10.1080/17429145.2015.1033023
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression and activity of antioxidant enzymes in barley (Hordeum vulgareL.) under controlled severe drought

Abstract: The objective of the present study was to determine the activity of antioxidant enzymes: superoxide dismutase (SOD), ascorbate peroxidase (APX), and catalase (CAT) and the expression of their genes in two barley genotypes under controlled severe drought. To fulfill this objective, 21-day-old barley plants of two genotypes: Rum and Yarmouk were exposed to controlled severe drought (25% field capacity) for 2, 9, and 16 days. The activity of SOD was significantly high in Rum genotype after 2 days of drought treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
53
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(67 citation statements)
references
References 27 publications
14
53
0
Order By: Relevance
“…On the other hand, inconsistent expression profile of SOD, CAT and POX genes with the corresponding enzyme activity under 25mM salt stress conditions was also recorded. In accordance with other researchers (Gill &Tuteja, 2010 andHarb et al, 2015), this finding could be attributed to the presence of isoforms of the antioxidant enzymes. At the biochemical level, the activities of all isoforms were assayed, whereas at the transcriptional level, the expression of only one isoform was examined (Furlan et al, 2013).…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, inconsistent expression profile of SOD, CAT and POX genes with the corresponding enzyme activity under 25mM salt stress conditions was also recorded. In accordance with other researchers (Gill &Tuteja, 2010 andHarb et al, 2015), this finding could be attributed to the presence of isoforms of the antioxidant enzymes. At the biochemical level, the activities of all isoforms were assayed, whereas at the transcriptional level, the expression of only one isoform was examined (Furlan et al, 2013).…”
Section: Discussionsupporting
confidence: 93%
“…The STBd line accumulated the lowest amount of MDA probably due to the rapid expression of the SOD, CAT, and POX antioxidant enzymes. Such antioxidant enzymes are considered as reliable indicators of environmental stress tolerance in plants (Harb et al 2015). These data correlate with those of Scandalios (1993), who reported that the efficient protection against oxidative damage caused by salt stress results from high SOD and CAT activities.…”
Section: Discussionsupporting
confidence: 69%
“…Moreover, it was recently reported that BRs induce apoplastic H 2 O 2 accumulation (Nie et al , Xia et al ), therefore analysis of an impact of BRs on the non‐enzymatic antioxidant system upon application of exogenous BR may become difficult to interpret because of this secondary H 2 O 2 ‐mediated effect, and also because the BR‐induced accumulation of H 2 O 2 results in stimulation of ABA biosynthesis (Zhou et al ). Therefore, the role of endogenous BRs in the regulation of non‐enzymatic antioxidant homeostasis under the control and drought conditions remains not fully elucidated, especially in crop species (Harb et al , Kka et al ).…”
Section: Discussionmentioning
confidence: 99%